2009
DOI: 10.1111/j.1756-1051.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Stachys ketenoglui sp. nov. (sect. Infrarosularis) (Labiatae/Lamiaceae) from south Anatolia, Turkey

Abstract: The new species Stachys ketenoglui Kaynak, Daşkın & Yılmaz (Lamiaceae) is described and illustrated from south Anatolia, Turkey. It is closely related to S. cataonica and S. pumila, but differs from them by its longer petiolated basal leaves, longer calyx, pale pink and longer corollas. Notes are also provided on its ecology, geographical distribution and conservation status. In addition, SEM photos of pollen grains for S. ketenoglui, S. cataonica and S. pumila are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Flowering and fruiting Stachys specimens were collected during field studies to the Taurus Mountains, south Anatolia in 2008 and 2009. The specimens were compared with relevant literature (Bhattacharjee 1974, 1982, Knorring 1977, Rechinger 1982, Davis et al 1988, Duman 2000, Dinç and Doğan 2006, İlçim et al 2008, Daşkın et al 2009) and with specimens of similar species from the (ANK) and (BULU) herbaria. Based on these comparisons we concluded that the collected specimens represent a hitherto undescribed species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowering and fruiting Stachys specimens were collected during field studies to the Taurus Mountains, south Anatolia in 2008 and 2009. The specimens were compared with relevant literature (Bhattacharjee 1974, 1982, Knorring 1977, Rechinger 1982, Davis et al 1988, Duman 2000, Dinç and Doğan 2006, İlçim et al 2008, Daşkın et al 2009) and with specimens of similar species from the (ANK) and (BULU) herbaria. Based on these comparisons we concluded that the collected specimens represent a hitherto undescribed species.…”
Section: Methodsmentioning
confidence: 99%
“…Stachys was revised by Bhattacharjee (1982) for the ‘Flora of Turkey’. In recent floristic studies, twelve new Turkish species have been found (Davis et al 1988, Duman 2000, Dinç and Doğan 2006, İlçim et al 2008, Daşkın et al 2009). In this paper, Stachys pseudobombycina is described as a new species.…”
mentioning
confidence: 99%
“…Stachys has 91 species, 22 subspecies and three varieties (116 taxa) belonging to 15 sections and two subgenera in Turkey. Of the 116 taxa, 55 (47.4 %) are endemic to Turkey [4][5][6][7][8][9][10][11][12][13][14][15][16]. The endemic taxa are mostly eastern Mediterranean elements.…”
Section: Introductionmentioning
confidence: 99%
“…Its taxonomic position is quite isolated [1]. Section Infrarosularis R. Bhattacharjee is represented in Turkey by 10 taxa belonging to 9 species which are all endemics [4,5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy two species were reported in a revision that R. Bhattacharjee conducted for the Flora of Turkey. Later studies have increased the species number to 90 (115 taxa), 54 of which 47% are endemic to Turkey (Bhattacharjee, 1982;Davis et al, 1982;Sümbül, 1990;Gemici and Leblebici, 1998;Duman, 2000;Dinç and Doğan, 2006;İlçim et al, 2008;Daşkın et al, 2009;Akçiçek, 2010;Yıldırımlı, 2010;Yılmaz et al, 2010; *Corresponding author. E-mail: sselvi2000@yahoo.com.…”
Section: Introductionmentioning
confidence: 99%